Intestinal carbohydrate absorption and permeability at high altitude (5,730 m). - Dinmore, A; Edwards, J; Menzies, I; Travis, S (1994)
To investigate the effects of high altitude on intestinal function, the absorption and permeation of nonmetabolizable carbohydrates were measured in 14 volunteers (median age 21 yr, range 19-37 yr) at sea level in Oxford, UK; at 1,050 m in Nepal; at 5,570 m after 5 days at > 5,500 m; and at 5,730 m after 11 days at > 5,500 m. Body weight decreased 5.7 +/- 1.19 kg from sea level to 5,570 m (P < 0.001 by paired t test) despite 72-h dietary records showing no change in energy intake. Absorption of carbohydrates by mediated transport was measured by urinary xylose and 3-O-methyl-D-glucose excretion. Xylose excretion (%oral dose) decreased from 31.4 +/- 4.5% to 20.7 +/- 4.5% (P < 0.001) and 3-O-methyl-D-glucose excretion decreased from 39.7 +/- 6.1 to 33.7 +/- 7.0% (P = 0.003) from sea level to 5,730 m. Monosaccharide permeation measured by L-rhamnose excretion decreased from 11.3 +/- 2.5 to 6.2 +/- 2.0% (P = 0.001). Intestinal permeability, a measure of barrier function (ratio of lactulose to L-rhamnose), increased from 0.036 +/- 0.014 at sea level to 0.084 +/- 0.042 at 1,050 m (P = 0.006), possibly due to infective enteropathy after arrival in Nepal, but reverted to normal (0.045 +/- 0.013; P = 0.062) at 5,730 m. Absorption of all carbohydrates returned to normal after return to the UK. This study showed that a decrease in mediated (D-xylose or 3-O-methyl-D-glucose) and diffusional (L-rhamnose) monosaccharide absorption occurs at high altitude but that intestinal permeability at 5,730 m is unchanged.